Legal regulation of public control over the activities of local government bodies in Ukraine - Chudyk, Nataliіa (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article discloses the legal regulation of public control over the activities of local self-government bodies, as a result of which the directions for its improvement determined by European integration in the conditions of modern democratic processes in Ukraine are determined.Legal provision of public control over the activities of local self-government bodies provides for: organization and regulation of the functioning of control subjects; methods and forms of implementation of public control and supervision; principles of interaction between local self-government bodies and control subjects; ensuring legality in conducting public control, as well as observing the rights and interests of the community and society. The system of normative legal acts in the field of public control over the activities of local self-government bodies includes: 1) the Constitution of Ukraine; 2) international legal acts; 3) laws of Ukraine; 4) subordinate legal acts.Public control over the activities of municipal bodies is ensured at the legislative level and is characterized in detail through local rule-making by local self-government bodies. Local self-government bodies enjoy broad discretionary powers in matters of organization and legal support of internal control. The legal concept of state control over the activities of local self-government bodies is in the process of formation. One of the key tasks of power decentralization was the establishment of a new approach to the organization of public control over the observance of legality during the exercise of own and delegated powers of local self-government bodies. In the national legal system, public control over the activities of local self-government bodies is established fragmentarily and conditionally. For the comprehensive development of democracy in Ukraine, we support the idea of enshrining the institution of public control in the Law of Ukraine "On Public Control".